1992
DOI: 10.1139/m92-126
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of 5-fluorouracil-induced infection with indigenous Escherichia coli in tumor-bearing mice by nonspecific immunostimulation

Abstract: We have previously reported that the lethal toxicity of 5-fluorouracil (5-FU) in specific-pathogen-free mice is due to an indigenous infection with Escherichia coli (K. Nomoto, T. Yokokura, Y. Yoshikai, et al. Can. J. Microbiol. 37:244-247, 1991). In the present study, we demonstrate that nonspecific immunostimulation augments host resistance against the lethal toxicity of 5-FU in tumor-bearing mice. Intravenous administration of a preparation of heat-killed Lactobacillus casei (LC 9018), a nonspecific immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Especially, 5-FU causes disturbances in the gastrointestinal microfl ora (Nomoto et al, 1992), systemic immunosuppression (von Bültzingslöwen et al, 1999) and impairment of the epithelial integrity (Hirata et al, 1999;Siber et al, 1980). Clinically, various symptoms, such as vomiting and heartburn, are recognized in patients when they take anti-tumor drugs for a long period (Polloni et al, 1986;Sartori et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, 5-FU causes disturbances in the gastrointestinal microfl ora (Nomoto et al, 1992), systemic immunosuppression (von Bültzingslöwen et al, 1999) and impairment of the epithelial integrity (Hirata et al, 1999;Siber et al, 1980). Clinically, various symptoms, such as vomiting and heartburn, are recognized in patients when they take anti-tumor drugs for a long period (Polloni et al, 1986;Sartori et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…A high dose of 5-FU would destroy the first line of defense, such as intestinal epithelial cells and immunocompetent cells derived from hematopoetic cells, -against intestinal microflora, leading to lethal translocation of intestinal microflora (21,26,31,41). CD8 ϩ i-IEL are located at the basolateral surfaces of i-EC, which are continuously exposed to numerous environmental antigens via the intestinal epithelium (18,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although 5-FU is a widely used antineoplastic agent, the cytotoxicity of 5-FU is not limited to tumor tissue. Hematopoietic cells and normal epithelial cells of the gastrointestinal tract are susceptible to 5-FU-induced cytotoxicity, which produces severe leukopenia and intestinal toxicity, leading to lethal translocation of intestinal microflora (21,26,31,41). We have previously reported that the number of CD8 ϩ i-IEL was severely reduced after 5-FU administration and that a nonapaeide thymic hormone, facteur thymique serique (FTS), accelerated recovery in a number of CD8 ϩ i-IEL following 5-FU administration and protected mice from 5-FUinduced bacterial translocation (22).…”
mentioning
confidence: 99%
“…Notably, 5-FU causes disturbances in the gastrointestinal microflora [2], systemic immunosuppression [3], and the impairment of epithelial integrity [4,5]. Clinically, patients who take anti-tumor drugs for long periods experience side effects such as vomiting and heartburn [6,7].…”
Section: Introductionmentioning
confidence: 99%